Transcription factors-regulated leaf senescence in major crops: Insights, applications, and challenges - Sen Li; Shichun Li; Shuya Tan; Zhonghua Liu; Zhonghai Li (Current Plant Biology)
Leaf senescence, the final stage of leaf development, is a complex biological process characterized by the degradation of macromolecules and nutrient redistribution. This process significantly contributes to plant fitness and adaptability. Senescence is regulated at multiple levels, including chromatin remodeling, transcription, post-transcription, translation, and post-translational modifications. Transcription factors play a pivotal role in regulating leaf senescence, with NAC and WRKY families being the most extensively studied. This review comprehensively summarizes recent advancements in understanding the regulatory roles of transcription factors in leaf senescence in important crops such as rice, wheat, maize, and soybean, and also briefly summarized significant findings in other crops such as sorghum, tomato, cotton, and cabbage. Additionally, we discuss molecular breeding strategies for optimizing crop performance through the manipulation of senescence by genetically engineering transcription factors.